2019
DOI: 10.1002/hed.25955
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant chemotherapy improves survival compared with concurrent chemoradiation alone in nasopharyngeal carcinoma patients with N3 disease

Abstract: Background Neoadjuvant chemotherapy (NAC) trials in endemic regions of nasopharyngeal carcinoma (NPC) found improved survival, but studies are lacking in nonendemic regions. We assessed whether adding NAC to concurrent chemoradiation (CRT) improves overall survival (OS), especially in high‐risk nonendemic patients. Methods Definitively treated NPC patients (n = 5424) from the National Cancer Database were analyzed for predictors of NAC and NAC effects on OS with multivariate Cox proportional hazards analysis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…Multimodal therapy in various combinations of surgery, radiation, or chemotherapy is used in the management of HN cancers, depending on the primary site and TNM stage (13)(14)(15). For nasopharyngeal carcinoma (NPC), treatment options include neoadjuvant chemotherapy (NAC), as it has high incidence of distant metastatic disease (16). Concurrent chemoradiation is the main approach for nonsurgical treatment of locoregionally advanced HN cancers (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Multimodal therapy in various combinations of surgery, radiation, or chemotherapy is used in the management of HN cancers, depending on the primary site and TNM stage (13)(14)(15). For nasopharyngeal carcinoma (NPC), treatment options include neoadjuvant chemotherapy (NAC), as it has high incidence of distant metastatic disease (16). Concurrent chemoradiation is the main approach for nonsurgical treatment of locoregionally advanced HN cancers (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…34 Poor survival outcomes of stage N3 were also noted in a large nonendemic data. 35 A recent validation study reported better predictive models with 8th staging, although T2 and T3 survival curves were similar. 36 In parallel, a nonendemic cohort from China was reported to have better prognostic separation for 8th classification in global stage and N stage, but not T stage.…”
Section: Discussionmentioning
confidence: 95%
“…Also excellent regional control rates of more than 90% were reported for N0–N2 tumors, dropping to 76.4 and 81.8% for N3a‐b according to AJCC 7th 34 . Poor survival outcomes of stage N3 were also noted in a large nonendemic data 35 . A recent validation study reported better predictive models with 8th staging, although T2 and T3 survival curves were similar 36 .…”
Section: Discussionmentioning
confidence: 97%
“…Nasopharyngeal carcinoma (NPC) is a malignant tumor that arises in the epithelial tissue of the head and neck. Approximately 87,000 new cases and 51,000 deaths of NPC are reported every year worldwide [1]. NPC shows a variant geographical distribution and is particularly endemic, prevailing in Southeast Asia and Southern China [2, 3].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a large scale of data are needed to identify the risk factors for metastases and therefore determine prognosis. T-classification and histological types of NPC are more likely to be correlated with metastasis because of the rich lymphatic network in and near the nasopharynx [1, 12, 13]. Both local recurrence and distant metastases are significant prognostic risk factors in NPC patients [14, 15].…”
Section: Introductionmentioning
confidence: 99%